2015
DOI: 10.1016/j.jpainsymman.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the International Consensus Definition of the Cancer Anorexia-Cachexia Syndrome (CACS) and Patient-Centered Outcomes in Advanced Non-Small Cell Lung Cancer

Abstract: The weight-based component of the recently proposed international consensus CACS definition is useful in identifying patients with advanced NSCLC who are likely to have significantly inferior survival and who will develop more precipitous declines in physical function and QOL. This definition may be useful for clinical screening purposes and identify patients with high palliative care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 48 publications
2
57
1
3
Order By: Relevance
“…Their overall Quality of Life was, as a result, lower than weight-stable patients. These findings are consistent with other reports evaluating the impact on patient outcomes, quality of life and survival in patients with cancer cachexia compared to weight-stable patients [21], [22]. As an example, a study by Wallengren and colleagues analysed secondary data from a large study performed on 331 cancer patients at a Swedish palliative care program.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Their overall Quality of Life was, as a result, lower than weight-stable patients. These findings are consistent with other reports evaluating the impact on patient outcomes, quality of life and survival in patients with cancer cachexia compared to weight-stable patients [21], [22]. As an example, a study by Wallengren and colleagues analysed secondary data from a large study performed on 331 cancer patients at a Swedish palliative care program.…”
Section: Discussionsupporting
confidence: 88%
“…"Weight loss, fatigue, and markers of systemic inflammation were the criteria for cancer cachexia that were most strongly and consistently associated with adverse QoL, reduced functional abilities, more symptoms, and shorter survival" [21]. Furthermore, in the study by LeBlanc and colleagues that compared advanced NSCLC patients with and without weight loss/cachexia (defined as ≥5% weight loss in prior 6 months or ≥2% weight loss with BMI<20 kg/m 2 ), it was found that survival, patient-reported outcome measures (FACT-G and specific domains from FAACT, FACIT-F, FACIT-L) and performance status (Karnofsky and ECOG) were all worse in the weight losing patients compared to non-weight losing patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight is easily measured in the clinic and it is important to have end‐points that can be implemented in clinical practice. From a patient perspective, weight loss is associated with psychosocial distress30, 31 whilst deteriorating physical function (e.g. performance status) is associated with reduced quality of life 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Cachexia is clinically relevant since it impacts on patients' quality of life, morbidity and mortality (25)(26)(27) . Nevertheless, the assessment of patients' nutritional status does not represent a priority in many clinical settings (28) .…”
Section: Clinical Relevance Of Cachexiamentioning
confidence: 99%
“…Cachexia is associated with worse outcome (25)(26)(27) . In order to develop effective therapies, it should be first assessed whether anabolic potential is still exploitable in patients with acute and chronic diseases.…”
Section: Anabolic Potential In Cachexiamentioning
confidence: 99%